Peningkatan Keterampilan Menulis Narasi Menggunakan Picture and Picture Pada Kelas V SDN 08 Pisang Kecamatan Pauh - Absari, Nina; Mahyuddin, Ritawati; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The purpose of this study is to describe the improvement of narrative writing skills by using the Picture And Picture model in Class V SD Negeri 08 Pisang Kecamatan Pauh Kota Padang. The subjects of this study are researchers as teachers who teach, and students who numbered 28 people. The type of research used is classroom action research. The approach used in this research is qualitative and quantitative approach. Research shows that teacher activity during learning process in cycle I that is 79 increased to 94 in cycle II, while result of research on student activity during process of learning in cycle I that is 69 increased to 92,3 in cycle II. Student learning outcomes at the pre-writing stage of 70,2 increased to 86,9, the writing stage of 60,2 increased to 80,3, the post-writing stage of 67,2,  increased to 84,1. It can be concluded  that the Picture and Picture model can improve students' narrative writing skills in Primary School.Keywords: Writing, naration, model, Picture and Picture